2020
DOI: 10.1021/acs.molpharmaceut.0c00396
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning the Interaction and Therapeutic Effect of Cu(II) Carbosilane Metallodendrimers in Cancer Cells: An In Vitro Electron Paramagnetic Resonance Study

Abstract: Copper(II) carbosilane metallodendrimers are promising nanosized anticancer metallodrugs. The precise control on their design enables an accurate structure-to-activity study. We hypothesized that different structural features, such as the dendrimer generation and metal counterion, modulate the interaction with tumor cells, and subsequently, the effectivity and selectivity of the therapy. A computeraided analysis of the electron paramagnetic resonance (EPR) spectra allowed us to obtain dynamical and structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…1 H, 13 C{ 1 H} and 31 P{ 1 H} NMR spectra were recorded on Bruker AV400PAS and AV300PAS (Bruker, Karlsruhe, Germany) instruments. 1 H and 13 C chemical shifts (δ, ppm) were measured relative to residual resonances of solvents.…”
Section: Analytical and Spectroscopic Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…1 H, 13 C{ 1 H} and 31 P{ 1 H} NMR spectra were recorded on Bruker AV400PAS and AV300PAS (Bruker, Karlsruhe, Germany) instruments. 1 H and 13 C chemical shifts (δ, ppm) were measured relative to residual resonances of solvents.…”
Section: Analytical and Spectroscopic Techniquesmentioning
confidence: 99%
“…1 H, 13 C{ 1 H} and 31 P{ 1 H} NMR spectra were recorded on Bruker AV400PAS and AV300PAS (Bruker, Karlsruhe, Germany) instruments. 1 H and 13 C chemical shifts (δ, ppm) were measured relative to residual resonances of solvents. High-resolution mass spectra were recorded using GCT Premier (Waters, Milford, MA, USA) and UPLC Xevo G2 Q TOF (Waters, Milford, MA, USA) mass spectrometers for chemical ionization and electrospray ionization, respectively.…”
Section: Analytical and Spectroscopic Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding system with Cu(OH 2 )Cl 2 moiety exhibits a moderate cytotoxicity in myeloid (U937) cancer cells. The system induces cell death through the mitochondria-lysosome system as well as vacuole formation through autophagy [129]. A comparative study of such G1 and G2 dendrimers conjugated with Cu(OH 2 )X 2 (27) (X: is ONO 2 ) and (28) (X is Cl) moieties (Figure 2) revealed that the increase in generation and changing nitrate with chloride, produced an increased in vitro cytotoxic effect in cervix (HeLa), normal and resistant breast cancer (MCF7 and HCC1806), advanced prostate cancer (PC3) and colorectal tumor (HT29) cell lines.…”
Section: Dendrimersmentioning
confidence: 99%
“…These modifications include the introduction of metal atoms that exhibit anticancer properties, for example, platinum, gold, silver, ruthenium or copper [ 6 , 20 ], into the dendrimer structure to improve their biomedical applications. In particular, carbosilane copper metallodendrimers bearing iminopyridine moieties have demonstrated outstanding anticancer activity in both solid tumors and myeloid cell lines [ 6 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%